MONOPULSE SECONDARY SURVEILLANCE RADAR ANTENNA FOR AIR TRAFFIC CONTROL (Perner's Contacts, 2011)
Secondary Surveillance Radar (SSR) play an important role in the Air Traffic Control of civilian and military aircrafts. It is frequently integrated with primary radars having antennas of both radars mounted on a common mast. Such an arrangement brings serious constrains on antenna size and weight. The design of a SSR antenna, for such an integrated arrangement is presented in the paper and solutions of the related problems are described.